(3fbhd eNJdaIs
(3ChdgG (B:s
(3ef EfTGA CHj GdaVd GdejOGfj(B: (3bGd aj UOQ cJGHg eLeY GdCeKGd(B: (3Ef CMSf eG jhTM Hg UOQ GdcdGe s
(3BNQgG (B:s
(3hCfG LGdS HLfH GdSdWGf efaQOkG CSJYQVge Hbdej s
(3efgG ef UOQ cJGH eLeY GdCeKGd ddejOGfjs
(3hQSGdI GdeaGNQI Hjf GdSja hGdbde dLeGd GdOjf Hf fHGJg hZjQgs
(3hHgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B165 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs